Evolution of Hindlimb Muscle Anatomy Across the Tetrapod Water‐to‐Land Transition, Including Comparisons With Forelimb Anatomy. Issue 2 (25th November 2018) - Molnar, Julia L.; Diogo, Rui; Hutchinson, John R.; Pierce, Stephanie E.
ABSTRACT: Tetrapod limbs are a key innovation implicated in the evolutionary success of the clade. Although musculoskeletal evolution of the pectoral appendage across the fins‐to‐limbs transition is fairly well documented, that of the pelvic appendage is much less so. The skeletal elements of the pelvic appendage in some tetrapodomorph fish and the earliest tetrapods are relatively smaller and/or qualitatively less similar to those of crown tetrapods than those of the pectoral appendage. However, comparative and developmental works have suggested that the musculature of the tetrapod forelimb and hindlimb was initially very similar, constituting a "similarity bottleneck" at the fins‐to‐limbs transition. Here, we used extant phylogenetic bracketing and phylogenetic character optimization to reconstruct pelvic appendicular muscle anatomy in several key taxa spanning the fins‐to‐limbs and water‐to‐land transitions. Our results support the hypothesis that transformation of the pelvic appendages from fin‐like to limb‐like lagged behind that of the pectoral appendages. Compared to similar reconstructions of the pectoral appendages, the pelvic appendages of the earliest tetrapods had fewer muscles, particularly in the distal limb (shank). In addition, our results suggest that the first tetrapods had a greater number of muscle‐muscle topological correspondences between the pectoral and pelvic appendages than tetrapodomorph fish had. However, ancestral crown‐group tetrapods appear to have had an even greater number of similar muscles (both in terms of number and as a percentage of the total number of muscles), indicating that the main topological similarity bottleneck between the paired appendages may have occurred at the origin of the tetrapod crown group. Anat Rec, 2018. © 2018 Wiley Periodicals, Inc. Anat Rec, 303:218–234, 2020. © 2018 American Association for Anatomy